2020
DOI: 10.1038/s41467-020-19737-2
|View full text |Cite
|
Sign up to set email alerts
|

Single cell RNA sequencing of human microglia uncovers a subset associated with Alzheimer’s disease

Abstract: The extent of microglial heterogeneity in humans remains a central yet poorly explored question in light of the development of therapies targeting this cell type. Here, we investigate the population structure of live microglia purified from human cerebral cortex samples obtained at autopsy and during neurosurgical procedures. Using single cell RNA sequencing, we find that some subsets are enriched for disease-related genes and RNA signatures. We confirm the presence of four of these microglial subpopulations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
454
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 485 publications
(481 citation statements)
references
References 41 publications
(95 reference statements)
26
454
1
Order By: Relevance
“…This subpopulation also co‐expressed APOE, a marker for neurodegenerative microglia 27 and low amounts of genes associated with antigen‐presentation and phagocytosis, consistent with the minor demyelinating activity in chronic active lesions. A microglia study in Alzheimer’s disease demonstrated a similar FTH1‐ expressing microglia phenotype 28 …”
Section: Discussionmentioning
confidence: 97%
“…This subpopulation also co‐expressed APOE, a marker for neurodegenerative microglia 27 and low amounts of genes associated with antigen‐presentation and phagocytosis, consistent with the minor demyelinating activity in chronic active lesions. A microglia study in Alzheimer’s disease demonstrated a similar FTH1‐ expressing microglia phenotype 28 …”
Section: Discussionmentioning
confidence: 97%
“…A single-nucleus RNA-seq included approximately 2000 microglial cells that increased the expression of the DAM genes: CD81 , APOE , SPP1 , CD74 , and HLA-DRB when compared to other microglial cells [ 78 ]. The opposing results were acquired in a recent scRNA-seq study of 11 post-mortem samples from patients with a mild cognitive impartment (MCI) and AD, and three control samples derived from the epileptic brains [ 79 ]. In line with the previous animal studies [ 72 , 77 ], the authors found that the expression of early DAM response genes increased in a proliferative cell cluster that appears predominant in the MCI/AD samples.…”
Section: Microglia In Neurological Diseases—insights From Single-cmentioning
confidence: 99%
“…In line with the previous animal studies [ 72 , 77 ], the authors found that the expression of early DAM response genes increased in a proliferative cell cluster that appears predominant in the MCI/AD samples. However, other DAM genes ( APOE , LPL , SPP1, CD74 ) were distributed across all clusters, with the highest expression in clusters enriched in cells from epilepsy-derived controls [ 79 ]. Such low consistency of the findings is surprising, but it may stem from using epilepsy-derived tissues as controls, as other studies have shown an induction of the DAM profile in epileptic subjects and a mouse model of epilepsy (see Section 3.3 ).…”
Section: Microglia In Neurological Diseases—insights From Single-cmentioning
confidence: 99%
See 1 more Smart Citation
“…In human AD, the microglia acquire a quite distinct signature characterized by the increased expression of “homeostatic” genes along with genes that are absent in the DAM signature (Zhou et al, 2020 ). Using single-cell RNA sequencing of live microglia purified from the human cerebral cortex, researchers have found at least one subset of cortical microglia that may be related to AD (Olah et al, 2020 ). Thus, the subset of cortical microglia related to AD should be prioritized in further validation efforts.…”
Section: Co-related Pro-inflammatory Molecules Between Systemic Inflamentioning
confidence: 99%